2015
DOI: 10.1039/c5tx00090d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vivo toxicity assessment of CdSe:ZnS quantum dots functionalized with EDTA-Bis-Cysteamine

Abstract: The design and surface chemistry of core shell quantum dots significantly affect their bio-distribution, kinetics and toxicity. Bis-ligands have been shown to improve the loading capacity and control the steric ligand packing density on the quantum dot surfaces, thus improving the biological properties and controlling the toxicity of the quantum dot nano-conjugates. In this study, we functionalized core shell CdSe:ZnS quantum dots with a homo-dimeric system (EDTA-Bis-Cysteamine) and evaluated their stability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The in vitro serum stability of MFSCNPs and MFSCNPs-FA-CHI-5FU nanocarriers was determined in serum samples by following the standard protocol . For serum stability experiments, 100 mL of 99m Tc labeled nanocarriers were incubated in 900 μL of the serum (in duplicate) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The in vitro serum stability of MFSCNPs and MFSCNPs-FA-CHI-5FU nanocarriers was determined in serum samples by following the standard protocol . For serum stability experiments, 100 mL of 99m Tc labeled nanocarriers were incubated in 900 μL of the serum (in duplicate) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro serum stability of MFSCNPs and MFSCNPs-FA-CHI-5FU nanocarriers was determined in serum samples by following the standard protocol. 28 For serum stability experiments, 100 mL of 99m Tc labeled nanocarriers were incubated in 900 μL of the serum (in duplicate) at 37 °C. Then samples were analyzed to check for any dissociation by instant thin layer chromatography (ITLC) using silica gel strips in developing solvent (0.9% NaCl aqueous saline solution).…”
Section: Synthesis Of Carbon Coatedmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Here we have synthesised a linear tetrapeptide GNGR (Gly-Asn-Gly-Asp) and conjugated it to a homodimeric N 2 S 2 ligand which is an EDTA-bis-cysteamine. In one of our earlier study 30 we have shown that this bis ligand very effectively controls the in vivo toxicity caused due to the leaching out of the Cd 2+ ions by providing a chelating effect. In this study we have tried to evaluate that if a specic targeting moiety is attached to this ligand then will there be an in vivo synergistic effect of active passive targeting or will only one of the mechanism predominate.…”
Section: Introductionmentioning
confidence: 95%